Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Is there a formal proof of this fact without using L'Hôpital's rule? I was thinking about using a proof of this fact: $$ \left.\frac{d(e^{x})}{dx}\right|_{x=x_0} = e^{x_0}\lim_{h\to 0} \frac{e^{h}-1}{h} = e^{x_0}\cdot 1=e^{x_0} $$ that I have to help prove: $$ \lim_{h\to 0} \frac{b^{h}-1}{h} = \ln{b} $$ Is there a succinct proof of this limit? How does one prove this rigorously?

share|cite|improve this question
Careful @arbautjc, I believe you need the derivative of ln to do that, which requires evaluating the limit in question. – Dylan Yott Mar 15 '13 at 11:44
I think you need only the derivative of $\exp$ (but, even if we need derivative of $\ln$, is it forbidden ?). Anyway, I removed my answer since it involves L'Hopital's rule and Rustyn explicitly wrote without L'Hopital's rule. – Jean-Claude Arbaut Mar 15 '13 at 11:50
up vote 5 down vote accepted

It is easy to see that $$\lim_{x\to 0}\frac{\log_a(1+x)}{x}=\log_a e$$ Now set $y=a^x-1$. So $a^x=1+y$ and then $$x=\log_a(1+y)$$ Clearly, when $x\to0$; $y\to 0$ so $$\lim_{x\to 0}\frac{a^x-1}{x}=\lim_{y\to 0}\frac{y}{\log_a(1+y)}=\log_e a$$

share|cite|improve this answer
good job, Babak! $\ddot\smile$ – amWhy Mar 16 '13 at 0:46

$$\lim_{x\to 0} \frac{\log_a(1+x)}{x} = \lim_{x\to 0} \frac{\log_e(1+x)}{x\log_e{a}}=\lim_{x\to0} \frac{\sum_{i=1}^{\infty} (-1)^{n+1} \frac{x^{n}}{n}}{x\log{a}} =\lim_{x\to 0} \frac{1+\sum_{i=2}^{\infty} (-1)^{n+1} \frac{x^{n}}{n}}{\log{a}} = \frac{1}{\log{a}} = \frac{1}{\frac{\log_a{a}}{\log_{a}{e}}} = \log_{a}{e}$$

Now set $y=a^x -1.$ Hence $a^x = 1+y$ and $$ x = \log_a(1+y) $$ As $x\to 0; y\to 0$
Therefore: $$ \lim_{x\to 0}\frac{a^x-1}{x}=\lim_{y\to 0}\frac{y}{\log_a(1+y)}=\log_e a $$

Thanks Babak.

share|cite|improve this answer
You are Welcome. I hope I could help you. – Babak S. Mar 17 '13 at 7:41

$$\text{ As }b=e^{\ln_eb}, \frac{b^h-1}h=\frac{e^{h\ln b}-1}h=\ln b\frac{e^{h\ln b}-1}{h\ln b }$$

$$\text{As, }\lim_{x\to 0}\frac{e^x-1}x=1,$$ $$\lim_{h\to0}\frac{b^h-1}h=\ln b\lim_{h\to0}\frac{e^{h\ln b}-1}{h\ln b }=\ln b$$

share|cite|improve this answer

$$\lim_{h\to 0}\frac{b^h - 1}{h}$$

Let $x = \frac{b^h - 1}{h}$ $$h.x = b^h - 1$$ $$b^h = hx + 1$$

Applying $\ln$ both sides

$$h\ln{b} = \ln{(hx+1)}$$ $$\ln{b}=\frac{\ln{(h.x+1)}}{h}$$ $$\ln{b}=\frac{\ln{(h.x+1)}}{hx}.x$$ Now when $h\to0$;$hx\to0$;$\frac{\ln{(h.x+1)}}{hx}\to ln(e);x\to \ln(b)$

Thus we can say

$$\lim_{h\to 0}\frac{b^h - 1}{h} = \ln(b)$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.